Near UV-Blue Excitable Green-Emitting Nanocrystalline Oxide - C. E. Rodríguez-García; N. Perea-López; G. A. Hirata (Advances in Materials Science and Engineering)
Green-emitting Eu-activated powders were produced by a two-stage method consisting of pressure-assisted combustion synthesis and postannealing in ammonia. The as-synthesized powders exhibited a red photoluminescence (PL) peak located at 𝜆=616 nm when excited with 𝜆=395 nm UV. This emission peak corresponds to the 5D0→7F2 transition in Eu3+. After annealing in ammonia, the PL emission changed to an intense broad-band peak centered at 𝜆=500 nm, most likely produced by 4f65d1→4f7 electronic transitions in Eu2+. This green-emitting phosphor has excitation band in the near UV-blue region (𝜆=300–450 nm). X-ray diffraction analysis reveals mainly the orthorhombic EuAlO3 and Al2O3 phases. Transmission electron microscopy observations showed that the grains are formed by faceted nanocrystals (~4 nm) of polygonal shape. The excellent excitation and emission properties make these powders very promising to be used as phosphors in UV solid-state diodes coupled to activate white-emitting lamps.